Stemness is Derived from Thyroid Cancer Cells - Ma, Risheng; Bonnefond, Simon; Morshed, Syed A.; Latif, Rauf; Davies, Terry F. (Frontiers in Endocrinology, 2014)
Background: One hypothesis for thyroid cancer development is its derivation from thyroid cancer stem cells (CSCs). Such cells could arise via different paths including from mutated resident stem cells within the thyroid gland or via epithelial to mesenchymal transition (EMT) from malignant cells since EMT is known to confer stem-like characteristics. Methods: To examine the status of stemness in thyroid papillary cancer we employed a murine model of thyroid papillary carcinoma and examined the expression of stemness and EMT using qPCR and histochemistry in mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf(V600E)/TPO-Cre). This construct is only activated at the time of thyroid peroxidase (TPO) expression in differentiating thyroid cells and cannot be activated by undifferentiated stem cells which do not express TPO. Results: There was decreased expression of thyroid specific genes such as Tg and NIS and increased expression of stemness markers such as Oct4, Rex1, CD15 and Sox2 in the thyroid carcinoma tissue from 6 week old BRAFV600E mice. The decreased expression of the epithelial marker E-cadherin and increased EMT regulators including Snail, Slug, and TGF-β1 and TGF-β3, and the mesenchymal marker vimentin demonstrated the simultaneous progression of EMT and the CSC-like phenotype. Stemness was also found in a derived cancer thyroid cell line in which overexpression of Snail caused up-regulation of vimentin expression and up regulation of stemness markers Oct4, Rex1, CD15 with enhanced migration ability of the cells. Conclusions: Our findings support our earlier hypothesis that stemness in thyroid cancer is derived via EMT rather than from resident thyroid stem cells. In mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf(V600E)/TPO-Cre) the neoplastic changes were dependent on thyroid cell differentiation and the onset of stemness must have been derived from differentiated thyroid epithelial cells.